2009
DOI: 10.1016/j.juro.2009.01.096
|View full text |Cite
|
Sign up to set email alerts
|

Vcsa1Acts as a Marker of Erectile Function Recovery After Gene Therapeutic and Pharmacological Interventions

Abstract: Purpose We identified molecular markers of erectile function, particularly those responding to erectile dysfunction treatment. Materials and Methods Sprague-Dawley retired breeder rats were intracorporeally injected with pVAX-hSlo, pSMAA-hSlo or the control plasmid pVAX. One week later the intracorporeal pressure-to-blood pressure ratio and gene expression were determined by microarray analysis and quantitative reverse transcriptase-polymerase chain reaction. Rat corporeal cells were transfected in vitro wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…19 Several recent reports have demonstrated that there is an endogenous NEP/APN inhibitor peptide called opiorphin in seminal plasma. [23][24][25][26][27] In rats, sialorphin, the opiorphin homologue, is primarily expressed in the corpus cavernosum, prostate, and the submandibular gland and its expression is under androgenic regulation. 23,28 The mean concentration of opiorphin in human semen is 12.9 + 1.8 ng/mL (mean + standard error of the mean).…”
Section: Neutral Endopeptidase and Sperm Motilitymentioning
confidence: 99%
“…19 Several recent reports have demonstrated that there is an endogenous NEP/APN inhibitor peptide called opiorphin in seminal plasma. [23][24][25][26][27] In rats, sialorphin, the opiorphin homologue, is primarily expressed in the corpus cavernosum, prostate, and the submandibular gland and its expression is under androgenic regulation. 23,28 The mean concentration of opiorphin in human semen is 12.9 + 1.8 ng/mL (mean + standard error of the mean).…”
Section: Neutral Endopeptidase and Sperm Motilitymentioning
confidence: 99%
“…The effects of CN injury on global gene expression in the MPG were explored by whole genome microarray expression analysis at both the 48‐h and 14‐day timepoints after CN crush injury. As previously described [22,23], we conducted a preliminary analysis showing that, 48 h after CN injury, 325 genes were differentially expressed ( P < 0.001, B > 4) compared to sham MPG. At 14 days after CN crush injury, 114 genes were differentially expressed.…”
Section: Resultsmentioning
confidence: 99%
“…We performed a total of seven micro‐array analyses using four chips for the silenced, and three chips for the control human corporal cells. Gene expression in the silenced cells was compared with controls using AffylmGUI software, available from http://www.bioconductor.org as previously described [23,30]. Data have been submitted to the NCBI Gene Expression Omnibus repository and can be accessed following the link http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?token=jzgpruaqyyiogbc&acc=GSE19672.…”
Section: Methods and Main Outcome Measuresmentioning
confidence: 99%